Helping land trusts prepare for a new climate: experiences of challenges and facilitators for translating knowledge about climate change adaptation in Ontario, Canada - Michael Drescher; Daria Koscinski; Jenna Quinn; Morgan Roblin (FACETS)
The environment is changing under the impact of climate change, but many Ontario land trusts still operate with the goal of maintaining historic patterns of biodiversity. This misalignment of conditions and goals may render the important work of these land trusts less effective. To help improve this situation, we conducted several knowledge translation activities to inform Ontario land trusts about possible climate change adaptation options. Throughout the knowledge translation activities, we collected participants’ comments and examined them with hypothesis and descriptive coding to reveal data about challenges and facilitators, which we grouped into themes with pattern coding. The results helped us identify challenges and facilitators that land trusts experience when participating in climate change knowledge translation and attempting to adapt to climate change. The challenges include a lack of resources, limited technical skills and species knowledge, and competing priorities and perspectives. Facilitators include a general interest in climate change, use of tools for adaptation planning, and resource sharing. To increase climate change adaptability in the Ontario land trust sector, we recommend greater collaboration between land trusts, modest modifications to existing conservation actions, shifting from passive to active conservation, and moving from species-level to community and ecosystem function conservation goals.